Freedom of the press in Iraqi legislation and its compatibility with international standards - Majeed, Soz Hamid; Karim, Bezhar Shawkat (Journal of Legal and Political Studies, 2023)
All constitutions in democratic and dictatorial countries have been keen on regulating the freedom of the press by allocating explicit texts in their constitutions، but most of them did not release this freedom. Restriction leading to depriving individuals from exercising or confiscating this right، unless this results in a constitutional violation based on the principle of legality. However، societies cannot progress without the presence of an effective and oversight authority at the same time، such as the control of the fourth authority represented by the press، given the role it represents as one of the most prominent means that support humanitarian organizations in their activities and help them pass their messages، and create a legal culture in various fields، exposing violations of human rights human rights، awareness campaigns for citizens، and news reporting to contribute to countries’ response to crises and disasters. This entails harmonizing internal legislation with established international standards in protecting press freedom.
Keywords: constitutions; explicit texts; constitutional violation; authority; humanitarian organizations